ANALYSIS OF INSTITUTIONAL AND REGULATION MODELS OF THE OIL SECTOR IN THE USA, BRAZIL, ARGENTINE, VENEZUELA AND SAUDI ARABIA - Machado, Luís Antônio Licks Missel; Triches, Divanildo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper aims to investigate the institutional and the regulation models of the production of oil of the United States, Brazil, Argentina, Venezuela and Saudi Arabia, especially contractual point of view and the level of government intervention. The theoretical conception of the regulation tends to accommodate the interests of lobbies politics, mainly the regulated industries and the consumers, as form of political support to the government. The oil is a strategical factor in the international economy. Govornments tend to support the producing companies of oil and they look for to participate in the profits for its extraction. Thus, it was demonstrated the five distinct realities how much to the production, consumption, capacity of refining and trade of the oil in the studied countries. It was also studied the forms of distinct institutional arrangements for which these countries regulate the exploration, either through contracts of concession and institutionalization of regulating agencies of the sector, as the United States, or only with contracts of concession as in Argentina. In the Venezuelan case, there is only a contract of joint-venture between the private initiative and the state-owned company. Saudi Arabia has an absolute monopoly in the oil sector of state property. In Brazil, there are a concession contract, regulating agency and one company of state capital.